Encapsulation of fatty acids in ruminant nutrition for improved meat and milk quality: A review - Besharati Maghsoud; Palangi Valiollah; Azhir Deniz; Lackner Maximilian (The EuroBiotech Journal)
In recent years, the methods of producing protected fat supplements for feed have greatly developed. As a means of preserving unsaturated fats from oxidation, encapsulation has been used by food industry researchers to reduce unpleasant odor and taste, and as an effective method of protecting unsaturated fats. The process of encapsulating involves covering or trapping the target substance(s) in another substance or system. Similarly, vitamins and micronutrient compounds in food do not remain stable for long and are subject to decomposition, which depends on chemical structure, food matrix characteristics, handling parameters, and storage conditions. Consequently, encapsulation can prevent these compounds from being destroyed until they are transferred to the right location or slow down decomposition processes (such as oxidation or hydrolysis). That concept can be expanded to lipids (oils and fats). Currently, emulsion spray drying is the most common method of fine oil microcoating. The mass formation method produces more stable microcoatings with higher oil content than spray drying, as recently discovered. Biodegradable polymers have gained much attention as encapsulation materials. Microencapsulated lipids can increase the meat and milk quality of ruminants.